ANALYSIS OF THE ROLE OF CHARACTERISTIC INFLUENCERS ON PURCHASE INTENTION MEDIATED BY CONSUMER WELL-BEING - Setyadan Adyuta; Panca Kurniati; Herna Rizaldi (STABILITY : Journal of Management and Business, 2025)
The rapid growth of social media users in Indonesia has made influencer marketing a dominant digital strategy, yet the psychological mechanisms through which influencer attributes affect consumer purchase decisions remain underexplored. This study investigates how influencer physical attractiveness, trustworthiness, and expertise influence purchase intention, with consumer well-being as a mediating variable. A quantitative approach was employed using purposive sampling of 161 Indonesian social media users aged 17 and above who actively follow influencers on visual platforms such as YouTube, Instagram, and TikTok. Data were collected via online questionnaires and analyzed using SmartPLS 3.0 with Structural Equation Modeling (SEM). Results show that trustworthiness and expertise significantly affect purchase intention, while physical attractiveness does not have a direct significant effect. Consumer well-being significantly influences purchase intention and mediates the effects of physical attractiveness and trustworthiness, but not expertise. These findings suggest that expertise operates through cognitive pathways, whereas physical attractiveness and trustworthiness work through emotional pathways. The study highlights how both cognitive and emotional mechanisms shape consumer behavior. Practically, brands should focus on influencer credibility and expertise, as well as create content that supports consumer emotional well-being to boost purchase intention.